Knowledge, Attitudes, and Practices Among Patients Undergoing Gastrointestinal Endoscopy in the Endoscopy Unit of a Tertiary-Care Hospital - Wei L; Niu Q; Ma L; Liu G; Zhang H; Zheng X; Lin Y; Du N; Li L (Patient Preference and Adherence)
Lianmin Wei,1,* Qing Niu,2,* Lili Ma,3 Guangxin Liu,4 Hongmei Zhang,2 Xiaoling Zheng,2 Yakun Lin,2 Ni Du,2 Lili Li2 1Department of Nursing, Dongying People’s Hospital, Dongying, Shandong Province, 257091, People’s Republic of China; 2Department of Digestive Endoscopy Center, Dongying People’s Hospital, Dongying, Shandong Province, 257091, People’s Republic of China; 3Department of Obstetrical, Dongying People’s Hospital, Dongying, Shandong Province, 257091, People’s Republic of China; 4Department of Gastroenterology, Dongying People’s Hospital, Dongying, Shandong Province, 257091, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lili Ma, Department of Obstetrics, Dongying People’s Hospital, No. 317 Dongcheng South 1st Road, Dongying, Shandong Province, 257091, People’s Republic of China, Email mali0363@126.comPurpose: Gastrointestinal endoscopy is a crucial diagnostic and therapeutic tool, but patients’ perspectives and preparation can significantly impact procedure outcomes. Understanding patient knowledge, attitudes, and practices (KAP) is crucial for improving the quality of care in gastrointestinal procedures, fostering informed consent, and enhancing patient outcomes. Our objective was to assess the KAP regarding gastrointestinal endoscopy in the Endoscopy Unit among those referred for diagnostic procedures.Patients and Methods: Patients scheduled for gastrointestinal endoscopy completed self-administered questionnaires to gather demographic information and evaluate their KAP scores. A total of 612 valid questionnaires were collected, 308 of which were filled out by male respondents (50.33%), with a mean age of 51.11 ± 12.61 years.Results: The mean KAP scores were 11.66 ± 3.95 (knowledge), 29.79 ± 3.27 (attitude), and 36.69 ± 4.99 (practice). Weak to moderate positive correlations were observed between knowledge, attitudes, and practices (knowledge-attitudes: r = 0.281, P < 0.001; knowledge-practices: r = 0.148, P < 0.001; attitudes-practices: r = 0.370, P < 0.001). According to structural equation modeling, knowledge directly impacted attitude (β = 0.397, P = 0.026), and attitude influenced practice (β = 0.402, P = 0.007). Knowledge indirectly affected practice via attitude (β = 0.159, P = 0.014).Conclusion: Patients demonstrated limited knowledge but exhibited positive attitudes and engaged in proactive practices regarding gastrointestinal endoscopy. These results highlight the importance of enhanced patient education programs in Endoscopy Units to improve knowledge and ensure informed decision-making regarding endoscopic procedures.Keywords: knowledge, attitude, practice, gastrointestinal endoscopy, endoscopy unit, cross-sectional study